A Study On The Influence Of Investor Psychology On Stock Market Trends At Bajaj Finserv, Nagpur - Halwale, Pratik Champat; Tekade, Atul (Journal of Neonatal Surgery, 2025)
Investor psychology plays a pivotal role in shaping stock market trends, significantly impacting investment decisions and market dynamics. The study explores the psychological factors influencing investors at Bajaj Finserv, Nagpur, including risk tolerance, behavioural biases, and decision-making patterns. By leveraging primary data from structured surveys and interviews, the research delves into how emotional and influence market activities. Secondary data from financial reports and stock performance analyses further substantiate the findings, offering insights into the correlation between investor sentiment and market fluctuations. The research reveals that market trends are not solely driven by economic fundamentals but are heavily influenced by collective investor behaviour, amplified during periods of volatility. The study underscores the importance of incorporating behavioural insights into financial strategies, enabling organizations and individual investors to make informed, rational decisions. Practical recommendations are provided to mitigate the adverse effects of psychological biases on investment outcomes. This research offers a unique perspective on integrating psychological and financial analysis to enhance understanding of stock market trends, contributing valuable insights to the field of behavioural finance.